Land of wolves, school of shepherds: the importance of pastoral knowledge on co-existence with large carnivores - Durá-Alemañ, C. Javier; Almarcha, Francisco; Sánchez-Zapata, José A.; Pérez-Ibarra, Irene; Morales-Reyes, Zebensui (Ecosystems and People, 2024)
The wolf (Canis lupus) is recovering and recolonizing its historic range in Europe. In places where wolves have long been absent, their recent recolonization could potentially provoke extensive livestock farmers’ opposition. To understand the conditions for extensive grazing-wolf co-existence, we conducted interviews with livestock farmers and shepherds to compare three Spanish regions in different wolf presence states: uninterrupted wolf presence, recent wolf recolonization and sporadic wolf presence. Our results show the importance of Traditional Ecological Knowledge (TEK) for reducing conflict and enabling co-existence. In areas where wolves were extinct and have been recently recolonized, loss of TEK has led to less of both tolerance to wolves and awareness of the benefits they provide. Conversely, in areas where wolf presence has been uninterrupted, maintaining the TEK associated with livestock management, such as use of mastiff dogs and shepherd's role, has favored the co-existence of extensive grazing systems with wolves. Our findings have important implications for the EU Common Agricultural Policy by highlighting the urgent need to integrate the close link between TEK and the co-existence of extensive grazing systems with large carnivores. Furthermore, the EU Nature Restoration Law could reinforce these same approaches. El lobo ( Canis lupus ) está recuperando y recolonizando su área de distribución histórica en Europa. En lugares donde los lobos han estado ausentes durante mucho tiempo, su reciente recolonización podría provocar la oposición de los ganaderos extensivos. Para comprender las condiciones de coexistencia de pastoreo extensivo con lobo, realizamos entrevistas a ganaderos y pastores para comparar tres regiones españolas en diferentes estados de presencia de lobo: presencia ininterrumpida de lobo, recolonización reciente de lobo y presencia esporádica de lobo. Nuestros resultados muestran la importancia del Conocimiento Ecológico Tradicional (TEK) para reducir los conflictos y permitir la ...